2014
DOI: 10.1055/s-0033-1363295
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial Comparing Buttressed versus Nonbuttressed Stapling in Patients Undergoing Pulmonary Lobectomy

Abstract: The efficacy of buttressed stapling in reducing the rate of air leak in patients undergoing pulmonary lobectomy could not be clearly demonstrated. However, air leak from stapler holes can be prevented with buttressed stapling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Unfortunately, most of these measures only yield modest results. In a phase III study comparing conventional staplers with devices reinforced by an attached polyglycolic acid sheet [25], no statistical differences were observed between both groups in intraoperative air leak frequency (63 vs. 63%) or postoperative duration (mean 3.5 vs. 2.9 days). A meta-analysis of 16 trials with 1642 randomized patients [26] showed that surgical sealants could effectively reduce time to chest tube removal, but this did not lead to reduction in length of postoperative hospital stay.…”
Section: Key Pointsmentioning
confidence: 96%
“…Unfortunately, most of these measures only yield modest results. In a phase III study comparing conventional staplers with devices reinforced by an attached polyglycolic acid sheet [25], no statistical differences were observed between both groups in intraoperative air leak frequency (63 vs. 63%) or postoperative duration (mean 3.5 vs. 2.9 days). A meta-analysis of 16 trials with 1642 randomized patients [26] showed that surgical sealants could effectively reduce time to chest tube removal, but this did not lead to reduction in length of postoperative hospital stay.…”
Section: Key Pointsmentioning
confidence: 96%
“…This product is mainly used to reinforce the suture site and prevent air leakage at the lung incision, and it has been widely used in the repair of bronchopleural fistula (21) and various refractory pneumothoraces (22). The effect of tubular Neoveil ® combined with an automatic cutting instrument in cutting lung tissue can effectively reduce the incidence of postoperative air leakage at the incision site (23,24). Furthermore, its high biocompatibility can effectively reduce the immune response induced by it being a foreign body (25).…”
Section: Discussionmentioning
confidence: 99%
“…The amount of intraoperative air leakage was evaluated according to the following scoring system: grade 0 ¼ no detectable air bubbles, 1 ¼ countable air bubbles, 2 ¼ stream of bubbles, and 3 ¼ coalesced bubbles (ie, air bubbles joining to form a continuous stream of air). 12 Additional suture repair was applied when an air leak was detected. Sealant materials such as fibrin glues, synthetic sealants, and collagen patches coated with fibrinogen and thrombin were used if an air leak persisted (Video 1).…”
Section: Treatmentmentioning
confidence: 99%
“…The duration of chest tube placement in group T was defined as 4.5 AE 2.52 days. 12 A reduction of the duration of chest tube placement by 1 day was considered to be clinically relevant. Using a statistical software program, a power-based analysis was conducted at a 2-sided significance level (a) of 0.05 and a power (1-b) of 0.9, which resulted in a value of 133.…”
Section: Sample Size Calculationmentioning
confidence: 99%